Spectroscopic Characterization of Croconate Bridging Complex: Conversion of Rhodizonate (C6O6 2-) to Croconate Bridging Ligand in a Pyridine Modified Large Macrocyclic Metal Arrangements (Journal of Bangladesh Academy of Sciences, 2016)
Rhodizonic acid (H2RHOD) was reacted with Co(PF6)2.6H2O in the presence of pyridine modified large macrocyclic ligand (H2Lopy) and triethylamine in N,N-dimethylformamide under argon atmosphere. Instead of [Co4(RHOD)2(Lopy)](PF6)2 (1), the main product of this reaction was a crystalline compound [Co4(CROC)2(Lopy)](PF6)2, which was isolated in low yield (< 25%). Based on the elemental analysis, ESI-mass spectroscopy, and infrared spectrum, the isolated compound was confirmed to be [Co4(CROC)2(Lopy)](PF6)2 (2), where CROC2- is croconate anion C5O52-.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 101-108, 2016